(untitled) (Research, Society and Development, 2022)
In view of the frequent questions regarding energy and its distribution, as a resource to be used by society and, as will be seen further on, a fundamental right, this paper seeks to analyze the expansion of Distributed Generation of energy in Brazil, having as a starting point, Aneel’s Resolution Number 482/2012, which regulated the implementation of the Electric Energy Consumption Compensation System. The context of the implementation of that System was analyzed, as well as the questions that arose over time. Using bibliographical researches, consisting of legal and theoretical texts from scholars in the area, it was possible to verify that the change in regulation abruptly carries with it all the signs of a violation of the principle of legal certainty (because it goes back more severely, harming investors sector) as well as the constitutional principle of preserving a balanced environment.